Comparative Study on the Impact of Family Therapy and CBT on General Health and Quality of Life of Couples - Mirdousti, Seyed Gholamreza; Asadi, JavanShir; Asadi, Javanshir; Bakhtiari Saeed , Bahram (Shahroud Journal of Medical Sciences, 2025)
Background: Psychosomatic issues are common among couples seeking divorce, with many experiencing anxiety, unexplained pain, gastrointestinal problems, and other symptoms, often showing significant improvement after therapy. This study aimed to evaluate the effectiveness of Cognitive-Behavioral Therapy (CBT) and Structural Family Therapy (SFT) in enhancing the general health and quality of life of couples seeking divorce.Methods: Thirty couples seeking divorce were referred to family counseling centers at the Minoodasht City Judiciary and met the inclusion criteria, were randomly selected and divided into two groups: CBT and SFT. Participants were assessed using general health and quality of life measures before and after Undergoing eight sessions of either CBT or Minuchin's structural family therapy. Post-test scores were compared between the two groups.Results: Paired t-test analysis revealed significant improvements in general health and quality of life scores for both therapy groups. Covariance analysis showed that both therapies were equally effective, with no significant differences in the level of improvement between the two groups.Conclusions: Both structural family therapy and cognitive-behavioral therapy significantly and equally improve the general health and quality of life of couples seeking divorce. Keywords: Cognitive-behavioral therapy, Structural family therapy, General health, Quality of life, Divorce.